(untitled) (Journal of the College of Basic Education, 2024)
The absorption and fluorescence spectra of the dye Copper-phthalocyanine (CuPc) in Dioxane solvent were separately studied under normal conditions at room temperature for three concentrations.(2x10-4, 1x10-4and 5x10-5) M. The intensities of the absorption and fluorescence spectra are increasing with the increase of the concentration which agrees with Beer – Lambert Law. Phthalocyanine molecules (CuPc) have two absorption bands in the visible and ultraviolet region of the spectrum. The higher energy band, occurring at around 350 nm, is generally known as the B-band. The lower energy band, occurring at around 650nm, is generally known as the Q-band. The measurement shows that the Absorption and Fluorescence spectrum have shifted to short wavelengths (Blue Shift). Additionally, the quantum efficiency increases with the decrease in concentration.